Analisis Gaya Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di SMK Wijaya Putra Surabaya - Nadia Salsabila; Ucik Rachmawati; Anugraheni Puspita; Sabrina Fitri Jasmine; Abella Fayza El Zahra; Rizky Rahmanjani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This study aims to analyze the principal's leadership style and its impact on improving teacher performance at the Wijaya Putra Vocational School in Surabaya. Effective leadership style can affect teachers' motivation, commitment, and involvement in carrying out their duties. This study uses qualitative methods involving interviews, observation, and document analysis as data collection tools. The impact of this leadership style is an increase in teacher performance at the Wijaya Putra Vocational School in Surabaya. Teachers feel motivated and engaged in the learning process, which is reflected in improved student achievement and parental satisfaction. The principal's leadership style also encourages collaboration and collaboration between teachers, strengthens a positive school culture, and promotes a conducive work climate. This research makes an important contribution to the development of education management and provides practical guidance for school principals in leading schools effectively.